KELARUTAN PIGMEN KUNING DAN HITAM ANORGANIK DALAM GELASI MIKROEMULSI WATER IN OIL DARI SISTEM AIR, TRITON X-100 DAN SIKLOHEKSANA UNTUK TINTA BALLPOINT - Yulianasari, Chindy (rc-institut, 2019)
The research for the solubility of yellow and black pigments in microemulsion water in oil system, triton X-100 and cyclohexane has been done. The purpose of this research is preparation of gels from the  microemulsion water in oil and determine the solubility of yellow and black inorganic pigment in gel from water in oil system, Triton X-100 and cyclohexane. The preparation of gel have done by the sol-gel method. Sol-gel is a process of forming inorganic compounds through chemical reactions in solutions at low temperatures. The formation of a gel from the water in oil microemulsion is carried out with the addition of the Tetra ethyl orto silicate and ethanol. The amount of the Tetra Ethyl ortho is added that is 1:8 comparison of  mol to the amount of water in the microemulsion water in oil. Tetra Ethyl ortho is subjected to hydrolysis with water forming gel. While ethanol serves as a TEOS organic solvent in the formation of gels. The result of  gels are semi-solid and have the ability to dissolve inorganic pigments larger than microemulsions. The average solubility of yellow pigment on the gel water in oil system, Triton X-100, and cyclohexane is 1.7 mg/g while the microemulsion is 0.6 mg/g, and black pigment solubility is 0.4 mg/g while the microemulsion is < 0.1 mg/g.